CD4+ T effector memory cell dysfunction is associated with the accumulation of granulocytic myeloid-derived suppressor cells in glioblastoma patients. Issue 6 (17th November 2015) - Dubinski, Daniel; Wölfer, Johannes; Hasselblatt, Martin; Schneider-Hohendorf, Tilman; Bogdahn, Ulrich; Stummer, Walter; Wiendl, Heinz; Grauer, Oliver M.
Abstract: Background: Myeloid-derived suppressor cells (MDSCs) comprise a heterogeneous population of myeloid cells that are significantly expanded in cancer patients and are associated with tumor progression. Methods: Multicolor flow cytometry was used to study the frequency, phenotype, and function of MDSCs in peripheral blood and freshly resected tumors of 52 participants with primary glioblastoma (GBM). Results: The frequency of CD14 high CD15 pos monocytic and CD14 low CD15 pos granulocytic MDSCs was significantly higher in peripheral blood of GBM participants compared with healthy donors. The majority of granulocytic MDSCs consisted of CD14 low CD15 high neutrophilic MDSCs with high T-cell suppressive capacities. At the tumor side, we found an increase in CD14 high CD15 pos monocytic MDSCs and high frequencies of CD14 low CD15 pos granulocytic MDSCs that displayed an activated phenotype with downregulation of CD16 and upregulation of HLA-DR molecules, which did not inhibit T-cell proliferative responses in vitro. However, a strong association between granulocytic MDSCs and CD4 + effector memory T-cells (TEM ) within the tumors was detected. Tumor-derived CD4 + TEM expressed high levels of PD-1 when compared with their blood-derived counterparts and were functionally exhausted. The respective ligand, PD-L1, was significantly upregulated on tumor-derived MDSCs, and T-cell co-culture experiments confirmed that glioma-infiltrating MDSCs can induce PD-1 expression on CD4 + TEM. Conclusions: Our findings provide a detailed characterization of different MDSC subsets in GBM patients and indicate that both granulocytic MDSCs in peripheral blood and at the tumor site play a major role in GBM-induced T-cell suppression.